2020
DOI: 10.1101/2020.10.30.20215335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innate immunity plays a key role in controlling viral load in COVID-19: mechanistic insights from a whole-body infection dynamics model

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a pathogen of immense public health concern. Efforts to control the disease have only proven mildly successful, and the disease will likely continue to cause excessive fatalities until effective preventative measures (such as a vaccine) are developed. It is important to better understand SARS-CoV-2 pathogenesis and population susceptibility to infection in order to develop effective disease management strategies. To this end, physiologically relev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…Although their modeling still requires validation, in their concept they concluded about the dominant role of innate immunity due to IFNs and macrophages as well as the importance of timing when initiating therapy. 84 Overall, the conclusions from all these QSP and pharmacodynamic studies are consistent with our thinking as we have discussed in the manuscript.…”
Section: Qsp Modeling To Estimate the Therapeutic Benefits Of Antiviral Therapysupporting
confidence: 79%
“…Although their modeling still requires validation, in their concept they concluded about the dominant role of innate immunity due to IFNs and macrophages as well as the importance of timing when initiating therapy. 84 Overall, the conclusions from all these QSP and pharmacodynamic studies are consistent with our thinking as we have discussed in the manuscript.…”
Section: Qsp Modeling To Estimate the Therapeutic Benefits Of Antiviral Therapysupporting
confidence: 79%
“…Variation in the time of activation of the adaptive immune response in different individuals implies that the SARS-CoV-2 virus can continue replicating and remains viable (31). In a recent study, it was found that interferons play a key role in suppressing the virus in the upper airway, while macrophages are primarily responsible for viral clearance in the lungs, mononuclear phagocyte system (MPS), and other systemic sites (32). Therefore, the rate at which lung and MPS macrophages clear the virus influences the viral load in both the lungs and the plasma (32).…”
Section: Dynamics Of Transmissionmentioning
confidence: 99%
“…In a recent study, it was found that interferons play a key role in suppressing the virus in the upper airway, while macrophages are primarily responsible for viral clearance in the lungs, mononuclear phagocyte system (MPS), and other systemic sites (32). Therefore, the rate at which lung and MPS macrophages clear the virus influences the viral load in both the lungs and the plasma (32). In patients with defective immune systems, viral clearance will depend on the excretion of the virus through the bile duct, which can take weeks.…”
Section: Dynamics Of Transmissionmentioning
confidence: 99%
“…While India continues to be on the corrective wave 2, Brazil is exhibiting an impulsive wave 3 that can be attributed to the revival of tourist attractions, beaches, shopping malls, and restaurants since October 2020 7 . It is important to note that in case of India, there is growing evidence that the Indian population possesses better innate immunity to SARS-CoV-2 8-10 , which indicates that any possible divergence from the sentiment-mediated wave principle may be a result of the additional biological variable at play in this population.…”
Section: Applying the Wave Principle To The Covid-19 Pandemicmentioning
confidence: 99%